OPTIMIZATION OF EXTRACTION CONDITIONS FOR ANDROGRAPHOLIDE USING FRACTIONAL FACTORIAL DESIGN - Mohamad Rafi (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Andrographolide is a major bioctive compound found in king of bitter (Andrographis paniculata). In this study, the extraction method and its condition were investigated in order to get an extract with maximum amount of andrographolide by comparing three other extraction methods, i.e. maceration, soxhletation and ultrasonication and also determination for the optimum condition of the selected extraction method. The highest andrographolide amount was found by maceration, so this method was choosen for further optimization of extraction condition. The optimum condition based on the prediction amount from 27 factor combinations was obtained in 360 times of extraction time, 2g/100mL of sample to solvent ratio, and 3fold of extraction frequency with prediction of andrographolide amount was 3.50%. While by using prediction profile, the optimum condition was obtained in 360min of extraction time, 2 g/100mL of sample and solvent ratio, and 4 times of extraction frequency with the amount was 3.47-3.74%.